2018
DOI: 10.1002/smll.201703734
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Preformed Au/Cu Nanoclusters Deposited on MgO Powders in the Catalytic Reduction of 4‐Nitrophenol in Solution

Abstract: clusters (nanoparticles) of tunable size typically below 10 nm are pre-assembled into a beam and then deposited in a vacuum chamber onto the catalyst support. [1][2][3][4] Potential advantages of the approach include the absence of solvent and effluent in the catalyst synthesis; control of cluster size, composition, and morphology; and the absence of ligands compared with colloidal routes. [5][6][7][8] However, the technique is at an early stage, [9] most especially where catalytic behavior under realistic rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 59 publications
0
59
0
Order By: Relevance
“…Furthermore,the traditional strategy of loading Au NCs on metal oxide and TiO 2 supports failed to achieve long-term stability under in situ illumination conditions, which limits the further development of catalysts based on Au NCs for practical application. [12] Thus,photostability over an extended period was explored by exposing Au@COF to irradiation with light (l > 420 nm) for 5h.T EM images showed that Au NCs supported on COF-S-SH maintained ultrafine and high dispersion after continuous light irradiation (Figure 3g,h). The result suggests that the ultrasmall pore structure of the COF and the strong S-Au binding energy provide double assurance for stabilizing Au NCs under light illumination conditions for an extended period of time.…”
Section: Research Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore,the traditional strategy of loading Au NCs on metal oxide and TiO 2 supports failed to achieve long-term stability under in situ illumination conditions, which limits the further development of catalysts based on Au NCs for practical application. [12] Thus,photostability over an extended period was explored by exposing Au@COF to irradiation with light (l > 420 nm) for 5h.T EM images showed that Au NCs supported on COF-S-SH maintained ultrafine and high dispersion after continuous light irradiation (Figure 3g,h). The result suggests that the ultrasmall pore structure of the COF and the strong S-Au binding energy provide double assurance for stabilizing Au NCs under light illumination conditions for an extended period of time.…”
Section: Research Articlesmentioning
confidence: 99%
“…Among various types of NPs,A uNPs as aprototype with adjustable size have drawn extensive attention for their excellent catalytic performance. [12] However,A uN Cs can be aggregated more readily than various other NCs and NPs for higher surface energy. [13] Thet raditional strategy of loading Au NCs on ametal oxide or SiO 2 has the disadvantage that it is difficult to maintain the stability of the composite under in situ photoirradiation conditions for al ong period of time, which is ab ottleneck for the development of catalysts based on Au NCs for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The 4‐NP isomer showed the k app value of 4.88 × 10 −3 s −1 . Au/Cu nanoclusters deposited on MgO powder was used as a catalyst for the reduction of NP . Similarly, other catalyst systems such as Ag/TiO 2 , copolymer/CuO nanocomposites, Co nanoparticles, Au‐supported carbon nanotube, and Zn nanoparticle functionalized aminoclay were used for the catalytic reduction of NP in the presence of NaBH 4 .…”
Section: Introductionmentioning
confidence: 99%
“…2 Au/Cu nanoclusters deposited on MgO powder was used as a catalyst for the reduction of NP. 3 Similarly, other catalyst systems such as Ag/TiO 2 , 4 copolymer/CuO nanocomposites, 5 Co nanoparticles, 6 Ausupported carbon nanotube, 7 and Zn nanoparticle functionalized aminoclay 8 were used for the catalytic reduction of NP in the presence of NaBH 4 . Ni nanoparticle encapsulated carbon nanotube was used as catalyst for the reduction chromium (VI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation